Knowledge and attitude about covid-19 Vaccination in pregnant women at Baqai Medical University - Dr. Saadia Akram; Farrukh Naheed; Nazish Ali; Naila Qamar; Farah Liaquat; Nikhat Ahsan (Journal of University Medical & Dental College, 2024)
Objective: The objective of this study was to explore the knowledge and attitude of pregnant women about Covid 19 vaccination.Methodology: A cross-sectional survey was conducted between 1st May 2022 to 30th November 2022 at OPD of Gynecology &Obstetric, Fatima Hospital, Baqai Medical University. This survey included women age 18-40 years seeking antenatal care through OPD and all pregnant women who were coming in emergency in active labour were excluded. A Pre-validated questionnaire was used in this study. Data was entered and statistical analysis was done using SPSS version 25.0 (IBM Corp., Armonk, NY, USA). Categorical variables were described using frequencies and percentages. Cross tabulation was done by using Chi-square test to assess the association between the respondents’ socio-demographic characteristics and their willingness to accept  the COVID-19 vaccine. A p-value of <0.05 was considered statistically significant.Result: Frequency of participants response to knowledge questions’56% had history of Covid 19 infection prior to pregnancy and conception.62% were vaccinated with vaccine other than Covid vaccine.65.8% did not receive Covid vaccine and upon asking if they are willing to receive ,only 27% answered positively.Conclusion: The study found that more than half of pregnant women were unable to receive Covid 19 vaccination more likely due to lack of awareness regarding the safety of vaccination during pregnancy.